THE EFFECTIVENESS OF USING COMBINATION OF MODIFIED GAME TIC TAC TOE AND JUMBLE WORD TO TEACH ENGLISH VOCABULARY OF DESCRIPTIVE TEXT TO THE SEVENTH GRADERS OF SMP NEGERI 1 CERME (RETAIN, 2014)
ABSTRACT English has four skills, they are listening, speaking, reading and writing. Those skill must be taught to the students, but they have to learn vocabulary first before learning those four skills. Vocabulary is a key in learning any language. The students have to enrich their vocabulary in order to make them success in learning those skills, especially for the students who in the seventh graders of junior high school. The writer chooses SMP Negeri 1 Cerme to conduct her research. The seventh grade students must be able to learn descriptive text but before they are success in making a good descriptive text, they have to enrich their vocabulary by learning English vocabulary of descriptive text first. In this case, the teacher must be creative to use technique to teach vocabulary to the students. Game is a technique that can be used by the teacher to teach vocabulary, one of game that can be used is combination of modified game Tic Tac Toe and Jumble Word. In conducting her research, the writer used an experimental quantitative by collecting the data through giving pretest before treatments were done then giving three treatments. Then giving post test after to get the students’ vocabulary score. But before pretest held, the writer gave a try out to other class not for classes which were chosen as experimental and control group. This try out was done to know whether the test could be the good test or not before it was given as pretest and posttest. The researcher analyzed quantitatively by using t-test to find out the significance difference in vocabulary mastery between the seventh graders who are taught using combination of modified game Tic Tac Toe and Jumble Word and those who are not. The writer found that t value was 3,76 with t table 2.00. It meant that there was significance difference in vocabulary mastery between the seventh graders who are taught using combination of modified game Tic Tac Toe and Jumble Word and those who are not. Based on the result of the research, the use of combination of modified game Tic Tac Toe and Jumble Word is appropriate technique to be used to teach English vocabulary of descriptive text to the students. Key Word : English Vocabulary, Combination of Modified Game Tic Tac Toe and Jumble Word, Vocabulary of Descriptive Text, Seventh Graders ABSTRAK Inggrismemilikiempatketerampilan, mendengarkan, berbicara, membacadanmenulis.Keterampilanitu harusdiajarkankepadasiswa. Namun merekaharusbelajarkosakataterlebihdahulusebelumbelajarempatketerampilan tersebut.Kosakataadalahkuncidalammempelajaribahasaapapun.Para siswaharusmemperkayakosa kata merekadalamrangkauntukmembuatmerekasuksesdalambelajarketerampilantersebut, terutamauntuksiswa yang di kelastujuh SMP. Disinipenulismemilih SMP Negeri 1 Cermeuntukmelakukanpenelitiannya.Siswakelastujuhharusmampubelajarteksdeskriptiftapisebelummerekasuksesdalammembuatteksdeskriptif yang baik, merekaharusmemperkayakosa kata merekadenganbelajarkosa kata bahasaInggrisdariteksdeskriptif lebih dahulu. Dalamhalini, guru haruskreatifuntukmenggunakanteknikuntukmengajarkankosakatakepadasiswa.Permainanadalahsuatuteknik yang dapatdigunakanoleh guru untukmengajarkankosakata, salah satu permainan yang dapatdigunakanadalahkombinasipermainanyang dimodifikasi Tic Tac Toe dan Jumble Word. Dalammelakukanpenelitiannya, penulismenggunakansebuahpenelitian kuantitatifdenganmengumpulkan data denganmemberikan pre-test sebelummemberikan tigatreatment.Kemudian setelah diberi pre-test dan treatment sebanyak tiga kali, penulis memberikan post-test.Namunsebelum pretest diadakan, penulismemberikan try out kepadakelas lain, dan tidakuntukkelas yang dipilihsebagaikelompokeksperimendankontrol. Try out inidilakukanuntukmengetahuiapakahtesbisamenjadites yang baikatautidak, sebelumitudiberikansebagai pre-test dan post-test. Penelitimenganalisissecarakuantitatifdenganmenggunakan t-test untukmengetahuiperbedaan yang signifikandalampenguasaankosakataantarasiswakelastujuh yang diajarkanmenggunakankombinasipermainan yang dimodifikasi Tic Tac Toe dan Jumble Word danmereka yang tidak. Penulismenemukanbahwanilai t test adalah 3,76dengan t tabel 2,00. Iniberartibahwaadaperbedaanyang signifikan dalam penguasaankosakataantarasiswakelastujuh yang diajarkanmenggunakankombinasipermainan yang dimodifikasi Tic Tac Toe dan Jumble Word danmereka yang tidak. Berdasarkanhasilpenelitian, penggunaankombinasipermainan yang dimodifikasi Tic Tac Toe dan Jumble Word adalahteknik yang tepatuntukdigunakanmengajarkosa kata bahasa inggris dalam teksdeskriptifkepadasiswa. Kata kunci : Kosa kata bahasa inggris, Permainan modifikasi Tic Tac Toe dan Jumble Word, Kosa kata dalam teks deskriptif, Siswa kelas tujuh